Both temporal and spatial aspects of predator management influence survival of a temperate ungulate through early life - McMillan, Brock R.; Hall, Jacob T.; Freeman, Eric D.; Hersey, Kent R.; Larsen, Randy T. (Frontiers in Ecology and Evolution, 2023)
Recent meta-analyses indicate that predator removal experiments result in marginal increases in prey abundance at best. However, most predator removal studies take place for less than the target prey’s generation time. We conducted multiyear coyote removals using a crossover experimental design and found that consecutive years of predator removal enhanced mule deer fawn survival more than did a single year of removal. We also found that removing coyotes from areas near fawn birth sites increased fawn survival, whereas removing coyotes from areas further from birth sites did not influence fawn survival. Our results underscore the need for coyote removal programs to 1) employ continuous removal efforts over consecutive years to maximize effectiveness, 2) employ spatially explicit removal efforts targeting fawning habitat, and 3) occur when the likelihood